2009
DOI: 10.1590/s0074-02762009000500007
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii: further studies on the subpellicular network

Abstract: The association of the pellicle with cytoskeletal elements in Toxoplasma gondii allows this parasite to maintain its mechanical integrity and makes possible its gliding motility and cell invasion. The inner membrane complex (IMC) Toxoplasma gondii is an important opportunistic pathogen that can lead to serious complications in congenitally infected newborns and in HIV-positive individuals and other immunocompromised patients (Israelski & Remington 1993, Luft et al. 1993, Wong & Remington 1994.In order to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This density underlies the IMC all around the cell and appeared continuous with the density originating from the polar rings at both the apical and the proximal ends of the sporozoite. We therefore presume that this density reflects the subpellicular network found in detergent‐extracted T. gondii tachyzoites (Mann and Beckers, 2001; Lemgruber et al. , 2009), which might serve to confer the crescent shape onto the sporozoite and endow it with the observed elasticity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This density underlies the IMC all around the cell and appeared continuous with the density originating from the polar rings at both the apical and the proximal ends of the sporozoite. We therefore presume that this density reflects the subpellicular network found in detergent‐extracted T. gondii tachyzoites (Mann and Beckers, 2001; Lemgruber et al. , 2009), which might serve to confer the crescent shape onto the sporozoite and endow it with the observed elasticity.…”
Section: Resultsmentioning
confidence: 99%
“…, 1997). A subpellicular network of filaments has been localized between microtubules and the IMC in T. gondii (Mann and Beckers, 2001; Lemgruber et al. , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…D’Haese et al ( 6 ) first showed that after several parasitic apicomplexans were subjected to nonionic detergent extraction, the resultant cell ghosts retained their full-length cellular shape even though in some cases the cortical microtubules extended for only half the length of the cells, suggesting the presence of an additional skeletal component (see also references 34 and 90 ). Mann and Beckers ( 8 ) made similar ghost preparations using Toxoplasma and detected a filamentous meshwork between the microtubules that they termed the subpellicular network and that we designate here the epiplast.…”
Section: Resultsmentioning
confidence: 99%
“…Several investigators have previously pointed out similarities between what we are calling epiplasts/epiplastins present in the euglenids and in the three alveolate radiations ( 21 23 , 45 , 46 , 49 , 67 , 90 , 106 , 133 , 139 , 148 ), and Santore ( 124 ) notes similarities between the epiplasts of euglenids and cryptophytes. In this study, we subjected these similarities to comprehensive scrutiny and also analyzed two additional lineages—the glaucophytes and cryptophytes—that had not been previously recognized as epiplastin producers.…”
Section: Discussionmentioning
confidence: 99%
“…The current status of knowledge places the motor machinery, which includes the myosin heavy and light chains and their anchoring proteins, tethered to IMC (98). The IMC is composed of flattened cisternae derived from the endomembrane system that extends beneath the entire surface of the parasite, except at its very apex, and is supported on their cytoplasmic side by microtubules and a network of ill-defined filaments (99)(100)(101)(102). The myosin driving parasite motility is myosin A (MyoA) (103)(104)(105), which belongs to an unconventional class of "neckless" myosins (class XIV) that is unique to Apicomplexa (103,106).…”
Section: The Motormentioning
confidence: 99%